Spatial Group of Housings. Six Case Studies in the Mediterranean Coast - Calleja-Molina, Manuel (Universidad de Lima. Carrera de Arquitectura, 2017)
Some residential architecture projects emphasize on understanding the concept of housing as a modular unit that will later be clustered to others based on three-dimensional geometric laws. This work is focused on six residential study cases located in the peninsular Mediterranean coast and assigned to this design strategy. Meter, layout and module are geometric tools used for analysis in this study, which method is basically graphic. The synthesis and the comparison of the sketches obtained provide new data to understand these buildings. Thus, similarities and divergences are revealed among their different laws and their association systems. At the same time, this study demonstrates how this methodology affects their users’ habitat approach.